Analisis Pengeluaran Pemerintah Bidang Kesehatan Bidang Pendidikan dan Infrastruktur terhadap Indeks Pembangunan Manusia (IPM) di Kabupaten Aceh Tamiang - Dhaifina Gasani; Nurlaila Hanum Hanum; Safuridar (Jurnal Samudra Ekonomika, 2020)
This study aims to determine the effect of government spending in the health on education and infrastructure on the Human Development Index (IPM) in Aceh Tamiang District. The data used are secondary data from 2008 to 2019. The data analysis method uses multiple lineir regression equations, hypothesis testing (t test and F test), and the coefficient of determination (R2) test. Statistical calculations using Microsoft Excel. The regression coefficient 0.015 represents government expenditure on health which has a positive effect on the Human Development Index. The regression coefficient of 0.038 represents government spending on education which has a positive effect on the Human Development Index. The regression coefficient of 0.007 represents government spending on infrastructure which has a positive effect on the Human Development Index. The results of the t test show that government spending in the health sector has a t sig> α5% (0.199> 0.05). It can be stated that government spending on health has no significant effect on the Human Development Index. The value of government expenditure in education is t sig> α5% (0.169> 0.05). It can be stated that government spending on education has no significant effect on the Human Development Index. The value of government spending on infrastructure is t sig> α5% (0.292> 0.05). It can be stated that government spending on infrastructure has no significant effect on the Human Development Index. The results of the F test, F sig <α5% (0.000 <0.05) can be stated that government spending on health, government spending on education and government spending on infrastructure have a significant effect on the Human Development Index in Aceh Tamiang District. The result of the determination coefficient test is 0.860 or 86%, the variable government spending on health, government spending on education and government spending on infrastructure affects the Human Development Index in Aceh Tamiang District. Keywords: Health, Education, Infrastructure, HDI Expenditures